The impact of corporate rebranding on brand equity and firm performance - Nana, S; Tobias, M.J; Chiliya, N (My University, 2019)
Rebranding has become a very important strategic tool for companies wanting to succeed in this ever-competitive business world using the principles of rebranding. Companies may occasionally discover that they may have to re-position the brand because customers change preferences and new competitors enter the market. Moreover, a strong brand enhances positive evaluations of a product’s quality, maintains a high level of product awareness, and provides a consistent image or brand personality. To keep up with fierce competition, companies may seek to transform their business due to changing business directions or adding extra business units. The main purpose of this study was therefore, to investigate the influence of rebranding on brand equity and firm performance. This study was quantitative in nature. Data were collected from 372 respondents using anonymously completed questionnaires. Research scales were operationalised on the basis of previous work. Proper modifications were made in order to fit the research context and purpose. “Rebranding” measure used five-item scales; “Store Layout” used a five item scale measure; “Franchising” used three item measure, “Brand Equity”; “ Perceived Quality “, “Brand Associations and Attributes” and “Firm Performance” all used a five item scale measure while “an customer experience ” used a six item scale measure. All measurement items were measure on a five-point Likert-type scale that was anchored by 1=strongly agree to 5= strongly disagree to express degree of agreement. The seven posited hypotheses were empirically tested. The results supported three hypotheses in a significant way and rejected four hypotheses. Important to note about the study findings is the fact that rebranding has no effect on the firm’s brand equity although brand equity has an influence on the firm’s performance. Notably too, the relationship between customer experience and firm performance is robust. This finding indicates that brand equity can have a strong influence without the influence of rebranding. A major implication for this study is that rebranding is a risky operation that needs to be carefully managed.
Keywords: Rebranding; Brand Equity; Firm performance